Abundance and distribution of pacific walrus Odobenus rosmarus divergens in vicinity of Cape Serdtse-Kamen in 2009-2013 - Maxim V. Chakilev; Anatoly A. Kochnev (Известия ТИНРО, 2014)
Results of the first special research of pacific walrus Odobenus rosmarus divergens at Cape Serdtse-Kamen conducted in the 2009-2011 and 2013 are presented. The coastal haulout place looks as series of relatively isolated areas (up to 36) located alongshore about 20 km from Cape Serdtse-Kamen to the Ikalyurynveem River mouth. Initially the walruses were on the northwestern edge of the haulout place between Cape Serdtse-Kamen and Cape Sulyn but expanded southeastward with increasing of their number. In the years with early and intense ice melting, the walruses come to the area in early September, and the haulout forms to the end of the first 10-day period of this month. In conditions of late ice retreat, as in the 2013, the walruses on the whole come to Cape Serdthse-Kamen later. The maximum number of walruses in this area was observed in 2009 (about 98,000 animals) and 2010 (118,500). This is the record number of walruses ever recorded simultaneously on one coastal haulout in the species range. Almost the whole Pacific population gathers in the vicinity of Cape Serdtse-Kamen for feeding in late autumn and continues to feed there until freezing of the Chukchi Sea. In spite of obvious significance of the area at Cape Serdtse-Kamen for the pacific walrus population, there still aren’t any special measures of their protection in this part of the coast when they are ashore - the measures are definitely necessary to prevent intensive economic activities in this key for the walruses area and to save the coastal haulout for traditional use of native people.